The North American arctic : themes in regional security - Menezes, Dwayne Ryan; Nicol, Heather N. (UCL Press, 2019)
The North American Arctic addresses the emergence of a new security relationship within the North American North. It focuses on current and emerging security issues that confront the North American Arctic and that shape relationships between and with neighbouring states (Alaska, Yukon, NWT, Nunavut, Greenland and Russia). Identifying the degree to which 'domain awareness' has redefined the traditional military focus, while a new human rights discourse undercuts traditional ways of managing sovereignty and territory, the volume's contributors question normative security arrangements. Although security itself is not an obsolete concept, our understanding of what constitutes real human-centred security has become outdated. The contributors argue that there are new regionally specific threats originating from a wide range of events and possibilities, and very different subjectivities that can be brought to understand the shape of Arctic security and security relationships in the twenty-first century. The North American Arctic provides a framework or lens through which many new developments are assessed in order to understand their impact on a changing circumpolar region at different scales -- from the level of community to the broader national and regional scale.